Development of an Inclusive City-Wide Faecal Sludge Management Business Model for Kabwe Town, Zambia - Moffat Tembo; Dr. Joel Kabika (International Journal of Engineering and Management Research, 2023)
Investment in sanitation solutions reduce disease burdens and is a huge market for public and private businesses since billons of people in the world do not have access to safely managed sanitation services. However, there remains much to be done to develop, pilot and scale up business models and technologies that work to fully understand the nature and quantities of faecal sludge needing collection and treatment. In Kabwe, the lack of a comprehensive business model informed by market research has contributed to faecal sludge not reaching designated treatment sites. Private operators charge unregulated fees for emptying and use unhealthy emptying methods that risk public health and groundwater resource. This research aimed at developing an inclusive city-wide FSM business model for Kabwe Town was conducted using mixed qualitative and quantitative approaches at 172 households and institutions spread across 20 wards. The results showed that 41 percent of the containments were unlined pits which could not be desludged easily. Atleast 84 percent of households could not afford to pay $42 for emptying services, but 96 percent were willing to contribute a monthly staggered tariff for emptying service which would make the service affordable regardless of socioeconomic status. It was estimated that at least 8,882m3/year of sludge would be available for emptying. With minimal overhead costs, utilising existing infrastructure and charging an emptying fee of $1 – $3 or $3 – $9/m3, the business would make a positive net profit in the first year of operations and offset a loan amount of upto to $28,400. The model demonstrated that in as much as financial resources are required, minimal start-up capital coupled with prudent planning, utilisation of readily available resources are key success factors. The study brought out key areas of attention which includes the need for awareness creation, pro-poor diverse payment schemes to increase demand and concerted stakeholders efforts on issues of policy, enforcement and capacity strengthening.